Impaired left ventricular filling rate induced by treatment with recombinant interleukin 2 for advanced cancer. Issue 2 (February 1994) - Fragasso, G.; Tresoldi, M.; Benti, R.; Vidal, M.; Marcatti, M.; Borri, A.; Besana, C.; Gerundini, P. P.; Rugarli, C.; Chierchia, S.
Abstract : BACKGROUND–Immunotherapy with recombinant interleukin 2 (rIL 2) has been extensively used to treat cancer but its use has been hampered by serious side effects including severe hypotension, arrhythmias, and myocardial infarction. OBJECTIVE–To assess the effects of rIL 2 on human left ventricular function. METHODS–Left ventricular (LV) function was monitored in 22 patients (9 women, 13 men) (mean (SD) age 53 (10) years) undergoing a 120 h continuous intravenous infusion of rIL 2 (18 x 10(6) IU/m2/day) for melanoma (4), renal cell (16), ovarian (1), and colon cancer (1). Radionuclide ventriculography was performed before and 1 h after the end of treatment. Ejection fraction (EF), peak emptying rate (PER), peak filling rate (PFR), and regional left ventricular wall motion were analysed. Heart rate (HR), central venous pressure (CVP), systolic (SBP) and diastolic blood pressures (DBP), the electrocardiogram, and myocardial enzyme concentrations were monitored throughout the study. RESULTS–All variables (mean (SD)) were normal before rIL 2 was given. After rIL 2 administration HR increased significantly from 84 (11) to 125 (18) beats/min (p < 0.0001), SBP fell from 128 (11) to 100 (9) mmHg (p < 0.001) and DBP from 76 (9) to 65 (7) mmHg (p < 0.0001). CVP decreased from 3.70 (3.2) to 1.30 (0.45) cm H2O (p < 0.001). EF (65 (7) to 64 (8%) and PER (3.56 (0.60) to 3.86 (0.83) EDV/s) did not change significantly. PFR decreased significantly at the end of the rIL 2 infusion from 2.68 (0.46) to 2.37 (0.43) EDV/s (p < 0.01). Left ventricular segmental hypokinesia developed in 6 patients. Myocardial enzyme concentrations remained normal throughout the study. CONCLUSIONS–The results of this study confirmed that rIL 2 produces important haemodynamic changes, predominantly related to decreased systemic resistance. However, the observed reduction in PFR in most patients suggested that rIL 2 might exert its action at the level of the heart muscle itself. The localised systolic dysfunction in some patients suggested that rIL 2 might also adversely affect myocardial perfusion.